Autoimmune and rheumatic manifestations and antinuclear antibody study in HIV-infected Thai patients - Kanokvalai Kulthanan (2018)
Background: There have been reports concerning an association between human immunodeficiency virus (HIV) infection and autoimmune and rheumatic diseases. Objective: The purpose of this study was to examine autoimmune and rheumatic manifestations in HIV-infected patients and their correlation with antinuclear antibody (ANA) tests. Methods: The clinical and laboratory results of HIV-infected patients attending the Department of Dermatology, Siriraj Hospital, Bangkok, Thailand, from February 1999 to January 2000, were analyzed. Laboratory studies included serum CD4 lymphocyte count and ANA tests. Results: Sixty-two patients were enrolled prospectively in the study. Myalgia was the most common clinical presentation (50%). Others included photosensitivity (on history) (39%), arthralgia (26%), vasculitis (18%), sicca complex (10%), arthritis (7%), and Reiter's syndrome (2%). A history of hair loss was given by 23% of patients. A positive ANA test was detected in 3%. No cases of systemic lupus erythematosus, scleroderma, or dermatomyositis were seen. Conclusions: Autoimmune and rheumatic manifestations were not uncommonly detected in patients with HIV infection. HIV infection may sometimes mimic systemic lupus erythematosus clinically.